Digital Literacy as a Support for Child Friendly Education in the Era of Technology Disruption - Rosyadi, Ratih Nurillah; Sarwi, Sarwi; Wasino, Wasino; Wardani, Sri (Proceedings of International Conference on Science, Education, and Technology, 2024)
The development of digital technology has changed the educational landscape, raising the need for digital literacy as a supporter of child-friendly education in the era of technological disruption. Digital literacy is the ability to use, evaluate, and participate in digital culture. However, digital literacy is not only about technical skills, but also about the ability to think critically and solve problems and interact with digital content ethically. The method used is a qualitative literature study research by collecting references from books and scientific journal articles. The research steps included generating a general idea, searching for information, focusing on the topic, identifying data sources, analyzing, and compiling the results. The results and discussion highlight the role of digital literacy in child-friendly education amid implementation challenges and opportunities. Digital literacy is an important foundation in supporting child-centered education in the era of technological disruption. Digital literacy enables children to understand, explore and use technology effectively and responsibly. Child-friendly education promotes a developmentally appropriate approach to children, keeping them safe and well when interacting with technology. Overall, digital literacy is an important pillar in child-friendly education in the era of technological disruption, equipping children with the ability to effectively participate in the digital world, face future challenges, and utilize technology to reach their full potential.